Numerical solutions for a two dimensional mountain wave model - DE, U. S.; FAROOQUI , S. M. T.; DEODHAR, A. G. (MAUSAM, 1975)
Numerical solutions for a two-dimensional linear mountain wave model for a baroclinic compressible atmosphere have been obtained. The techniques developed for smaller obstacles have been suitably adopted for equation application to extended topographic features with, real air stream characteristics. Computations for different situations when mountain wave observations were available have been made. Important aspects of the results have been diabatic discussed.